Epidemiological analysis of trypanocidal drug resistance in Zebu cattle in Ghibe, southwest Ethiopia. Abstract - Rowlands, G.J.; Nagda, S.M.; Leak, S.G.A.; Mulatu, W.; D'Ieteren, G.D.M.; Peregrine, A.S. (OAU/STRC, 1999)
It is useful to be able to estimate the incidence of new infections in cattle exposed to a high challenge of drug resistance trypanosomes; with this information the impact of an intervention that improves the control of trypanosomosis can be better understood. Approximately 750 Ethiopian Highland village zebu cattle exposed to high levels of drug resistance have been monitored monthly in the Ghibe valley, Southwest Ethiopia from 1986 to 1997. When inoculated into Boran calves all isolates obtained from cattle at Ghibe were found to be resistant to diminazene aceturate. Throughout the period of monitoring all cases of parasitaemia detected when the packed red cell volume (PCV) was less than 26 percent have been treated with diminazene aceturate at 3.5 mg/kg body weight. Eighty five per cent of infections were due to Trypanosoma congolense and 15 percent to T. vivax. The pattern of decreasing prevalence of trypanosome infection with increasing PCV was evident. Fewer than 5 percent of samples were found to be parasitaemic when PCV > or = 26 percent. Thus, taking into consideration the level of sensitivity of the phase contrast/buffy coat technique for the detection of trypanosomes, it was assumed that only when PCV was > or = 26 percent or higher and no trypanosomes were detected was the sample likely to be free of infection. Thus, when trypanosomes have been detected in an animal following two months with no parasitaemia detected and with a PCV greater than or equal to 26 percent the parasitaemia has been assumed to be associated with a new infection. Using this definition, the mean incidence of T. congolense infections in cattle over the study period was 13.7 percent and the overall prevalence of such infections was 22.6 percent. The difference between these figures gives a measure of the apparent prevalence of recurrent infections detected as parasitaemic. In contrast to T. congolense, T. vivax infections appeared to be drug-sensitive since the incidence and prevalence of infections with the species were both 4 percent. However, laboratory drug sensitivity experiments have not been undertaken for T. vivax to confirm this observation. In general the overall infection incidence correlated better than infection prevalence with tsetse relative density. This gives credence to our definition of new infections in cattle. This method for defining new infections was applied to investigate the effect of tsetse control using an insecticidal cypermethrin `pour-on' applied over a period of five years on the incidence of trypanosomal infections and prevalence of recurrent infections in one of the herds. Tsetse control resulted in a 72 percent reduction in the incidence of new infections and a 58 percent reduction in the apparent prevalence of recurrent infections detected as parasitaemic. In view of the very high prevalence of drug resistant trypanosomes as demonstrated under laboratory conditions. it would appear, from the apparent reduction in prevalence of recurrent infections, that the cattle at Ghibe were able to develop a better immune response to infection when the tsetse challenge was reduced. Combined methods of tsetse control and chemotherapy have thus been able to reduce the negative effects of trypanosomosis on the health and productivity of the cattle.